PENGARUH TINGKAT SUKU BUNGA SBI TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR SEMEN YANG TERDAFTAR DI BEI - Sari, Diah Rachma (Jurnal Akuntansi AKUNESA, 2014)
The interest rate is a variable that is always considered by investors before making an investment decision. One is tingakt SBI. This research is used to determine the effect of interest rate SBI influence on stock prices of cement sub-sector company listed on the Stock Exchange. Based on the analysis of the research conducted can be concluded that the SBI rate and a significant negative effect on stock prices of cement sub-sector company listed on the Stock Exchange consisting of PT. Holcim Indonesia Tbk, PT. Indocement Tbk and PT. Semen Indonesia (Persero) Tbk period 2010-2012. This is evidenced by the results of a simple regression analysis and testing of the regression coefficients of a number of sub-samples of the cement sector companies listed on the Stock Exchange.Keywords: SBI interest rates, stock price